Comparison of adequacy of anaesthesia monitoring with standard clinical practice monitoring during routine general anaesthesia: An international, multicentre, single-blinded randomised controlled trial - Gruenewald, Matthias (Eur J Anaesthesiol, 2021)
BACKGROUND: Previous studies have suggested that monitoring the levels of both hypnosis and antinociception could reduce periods of inadequate anaesthesia. However, the evidence regarding associated benefits of this monitoring is still limited. OBJECTIVE: The primary objective of this study was to confirm that guidance of anaesthesia by depth of hypnosis and antinociception monitoring decreases the number of inadequate anaesthesia events in comparison with standard clinical practice. DESIGN: A multicentre, single-blinded, randomised controlled trial. SETTING: The study was conducted in four European University hospitals in four different countries between December 2013 and November 2016. PATIENTS: The study population consisted of a total of 494 adult patients undergoing elective surgery requiring tracheal intubation. INTERVENTIONS: The patients were allocated to one of two groups. The first group was treated using Entropy for depth of hypnosis and surgical pleth index to determine depth of antinociception (adequacy of anaesthesia group; AoA group). The second group was monitored using standard monitoring alone (control group). Anaesthesia was conducted with target-controlled infusions of propofol and remifentanil. MAIN OUTCOME MEASURES: The primary outcome of the study was the number of total unwanted events for example signs of inadequately light or unintentionally deep anaesthesia. RESULTS: Evidence of inadequate anaesthesia had an incidence of around 0.7 events per patient in both groups with no difference between groups (P = 0.519). In the AoA group, the overall consumption of propofol was significantly reduced (6.9 vs. 7.5 mg kg(−1) h(−1), P = 0.008) in comparison with the control group. The consumption of remifentanil was equal in both groups. The times to emergence [8.0 vs. 9.6 min (P = 0.005)] and full recovery in the postanaesthesia care unit (P = 0.043) were significantly shorter in the AoA group. No differences were seen in postoperative pain scores or in the use of analgesics. CONCLUSION: In the current study, the guidance of total intravenous anaesthesia by Entropy and surgical pleth index in comparison with standard monitoring alone was not able to validate reduction of unwanted anaesthesia events. However, there was a reduction in the use of propofol, and shorter times for emergence and time spent in the postanaesthesia care unit. TRIAL REGISTRATION: at ClinicalTrials.gov NCT01928875.